Chlorpropamide-alcohol flushing and large-vessel disease in non-insulin-dependent diabetes. Issue 6235 (26th July 1980) - Barnett, A H; Pyke, D A
Abstract : A total of 220 non-insulin-dependent diabetics aged over 45 (139 with a history of chlorpropamide-alcohol flushing and 81 without such a history) were examined for the prevalence of large-vessel disease. Large-vessel disease was significantly more common in the group without a history of flushing (41% v 24% of the two groups respectively; p < 0.05). A history of myocardial infarction was found in 14 (17%) of the patients without flushing but in only 10 (7%) patients with flushing. Similar differences were detected in the prevalences of angina, intermittent claudication, and absent foot pulses. There were, however, no significant differences in the prevalence of cerebrovascular disease or hypertension between the two groups. These results suggest that patients with non-insulin-dependent diabetes who flush in response to chlorpropamide and alcohol are significantly less likely to develop large-vessel disease than those who do not. Hence such flushing is probably related to the pathogenesis not only of small-vessel but also of large-vessel disease.